Multidisciplinary Approach to the Diagnosis and In-Hospital Management of COVID-19 Infection: A Narrative Review - Lo Bianco, Giuliano; Di Pietro, Santi; Mazzuca, Emilia; Imburgia, Aurelio; Tarantino, Luca; Accurso, Giuseppe; Benenati, Vincenzo; Vernuccio, Federica; Bucolo, Claudio; Salomone, Salvatore; Riolo, Marianna (Frontiers in Pharmacology, 2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2 or Covid-19) was declared a pandemic on 11th March 2020 by the World Health Organization. This unprecedented circumstance has challenged hospitals’ response capacity, requiring significant structural and organization changes to cope with the surge in healthcare demand and to minimize in-hospital risk of transmission. In addition, as our knowledge advances, we now understand that Covid-19 is a multi-systemic disease rather than a mere respiratory tract infection, therefore requiring holistic care and expertise from various medical specialties. The aim of this manuscript is to provide a comprehensive and multidisciplinary review of the current scientific evidence on Covid-19 across several medical specialties involved in the clinical management of these patients.